PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL TERHADAP PRESTASI BELAJAR IPA SISWA KELAS IV SEMESTER GANJIL SDNEGERI 1 JOTON JOGONALAN KLATEN TAHUN PELAJARAN 2015/2016 - Heri Bayu Prasetyo; V. Renyaan Renyaan (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
The purpose of this research in a descriptive manner is to know the learning achievement’s preference of fourth grade students at negeri 1 Joton elementary school in the academic year 2014/2015 which the learning uses audiovisual media and the learning don’t audiovisual media. According to comparative, to know the differences of science learning achievement students of four grade in odd semester at negeri 1 Joton elementary school in the academic year 2014/2015 between taught with audiovisual media and without audiovisual media. The results showed that the tendency of science learning achievement of fourth grade students of at negeri 1 Joton elementary school in the academic year 2014/2015 a which the learning uses audiovisual media, including very high category on the average of 23.500 and learning without the use of audiovisual media in the high category with a average of 18,500. In the t-test obtained thitung = 3.999 and p = 0.001, for p <0.01 then the comparability of results of the t-test is concluded that there are very significant differences in learning achievement IPA fourth grade students of at negeri 1 Joton elementary school between learning using media audiovisual and without the use of audiovisual media.